Application of kDNA Minicircle PCR-RFLP to Characterize Leishmania donovani Clinical Isolates Obtained from Post-Kala-Azar Dermal Leishmaniasis in Eastern Nepal. (30th July 2019) - Pokhrel, Ojesh; Rai, Keshav; Bhattarai, Narayan Raj; Rijal, Suman; Rijal, Arpana; Khanal, Basudha
Abstract : Post-kala-azar dermal leishmaniasis (PKDL) is a skin manifestation of visceral leishmaniasis (VL) which develops after apparent cure in some patients. PKDL is considered as the potential reservoir for the VL infection. Molecular epidemiological characterization of L. donovani isolates obtained from VL and PKDL isolates is essentially required in order to understand the transmission dynamics of the VL infection. To date, genetic variation among the VL and PKDL L. donovani isolates was not fully elucidated. Therefore, 14 clinical isolates from VL and 4 clinical isolates from PKDL were speciated by hsp70 and rDNA genes. Further characterization of L. donovani by haspB PCR demonstrates two different genotypes. All PKDL isolates have the same genetic structure. kDNA PCR-RFLP assay revealed 18 different genotypes; however, structural analysis showed the two distinct kDNA genotype population ( k  = 2). The kDNA fingerprint patterns of parasites from hilly districts were clustered separately from low-land districts. Therefore, further study with a large number of samples is urgently required for systematic characterization of the clinical isolates to track the molecular epidemiology of the Leishmania donovani causing VL and the role of PKDL as a reservoir.